Human mercury exposure and adverse health effects in the Amazon: a review Exposição humana ao mercúrio e efeitos adversos à saúde na Amazônia: uma revisão - Carlos J. S. Passos; Donna Mergler (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
This paper examines issues of human mercury (Hg) exposure and adverse health effects throughout the Amazon region. An extensive review was conducted using bibliographic indexes as well as secondary sources. There are several sources of Hg (mining, deforestation, reservoirs), and exposure takes place through inhalation or from fish consumption. There is a wide range of exposure, with mean hair-Hg levels above 15µg/g in several Amazonian communities, placing them among the highest reported levels in the world today. Dietary Hg intake has been estimated in the vicinity of 1-2µg/kg/day, considerably higher than the USEPA RfD of 0.1µg/kg/day or the World Health Organization recommendation of 0.23µg/kg/day. Neurobehavioral deficits and, in some cases, clinical signs have been reported both for adults and children in relation to Hg exposure in several Amazonian countries. There is also some evidence of cytogenetic damage, immune alterations, and cardiovascular toxicity. Since fish provide a highly nutritious food source, there is an urgent need to find realistic and feasible solutions that will reduce exposure and toxic risk, while maintaining healthy traditional dietary habits and preserving this unique biodiversity. Este artigo examina questões sobre exposição humana ao mercúrio (Hg) e seus efeitos adversos à saúde na Amazônia, com base em extensa revisão da literatura. Diferentes bioindicadores revelam uma ampla faixa de exposição, com teores médios de Hg em cabelo acima de 15µg/g em diversas comunidades amazônicas, situando-as dentre as mais expostas no mundo atualmente. Taxas de ingestão diária de Hg foram estimadas em alguns estudos e situam-se entre 1-2µg/kg/dia, consideravelmente acima das doses de referência estabelecidas pela USEPA (0,1µg/kg/dia) ou pela OMS (0,23µg/kg/dia). Déficits neurocomportamentais e, em alguns casos, sinais clínicos relacionados à exposição mercurial têm sido relatados tanto em adultos quanto em crianças de diversos países amazônicos. Há também evidências de dano citogenético, mudanças imunológicas e toxicidade cardiovascular. Visto que peixe é altamente nutritivo e há diversas fontes de Hg nesta região, existe uma necessidade urgente de encontrar soluções realistas e viáveis capazes de reduzir os níveis de exposição e de risco tóxico, ao mesmo tempo mantendo os hábitos alimentares tradicionais, preservando a biodiversidade píscea e frutífera e melhorando a saúde das populações desfavorecidas e afetadas.